IMPROVING THE ACTION MEANS FOR THE DEVELOPMENT OF THE MAIN PSYCHO-MOTOR SKILLS THAT ARE SPECIFIC TO THE LUGE EVENT IN THE JUNIOR ATHLETES OF THE VATRA DORNEI SCHOOL SPORTS CLUB - Balint G.; Rusoiu I. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
Being in direct contact with the national luge elite, we thought that an analysis regarding the actual conditions during the training process for developing the main psycho-motor skills that are specific to the luge event, could be beneficial, and it could lead to a revival of the sleigh training that the federation, and us, are long waiting for.The research was conducted in three stages:Stage I: October 13-20, 2011;Stage II: January 7-12, 2012;Stage III: February 21-28, 2012.Before starting the experiment, we elaborated certain training plans (annual, stage, cycle) that we consider to be actually a "Training model".These plans were destined for the experimental group, the witness group conducting their activity according to their normal schedule.From the analysis of the results recorded during the experimental activity, we observed in the final phase of the research that the results obtained by the experimental group are superior to the ones recorded by the witness group, a fact that can be seen also in the tables and figures presented in the paper.